ANALISIS DAN IMPLEMENTASI RANGKAIAN RCD SNUBBER PADA RANCANG BANGUN DC-DC FLYBACK CONVERTER - Fernando, Bagas; Djuriatno, Waru; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
DC-DC Converters are essential components in modern power systems that convert DC voltage from one level to another. These converters are used in various applications, ranging from electronic devices to industrial needs. One commonly used topology is the DC-DC flyback converter due to its simple design, although it often faces voltage spikes caused by parasitic inductance that can damage the MOSFET. This study designs an RCD snubber circuit to address these voltage spikes. The snubber circuit consists of a resistor, capacitor, and diode installed on the primary winding of the flyback converter transformer. Testing results indicate that the RCD snubber successfully reduces voltage spikes, despite some power dissipation in the resistor. Overall, this circuit effectively protects components from high voltage spikes. Keywords: DC-DC flyback converter, RCD snubber, voltage spikes, power dissipation.